RISKS FOR ABUSE AND NEGLECT OF ELDERS WITH COGNITIVE IMPAIRMENT OR DEMENTIA: INSIGHTS FROM THREE GROUPS. (16th November 2018) - Lee, J; Sun, F; Chima, E
Abstract: Purposes. Cognitive impairment due to Alzheimer's disease and related dementia places elders at a high risk for abuse and neglect. This study aims to identify risk factors for abuse and neglect of elders with dementia or cognitive impairment, and to develop strategies to prevent abuse and neglect from integrated perspectives of patients, family caregivers, and helping professionals. Method. Using semi-structured interviews, six focus group discussions were conducted consisting of fourteen service professionals (Mage=55.7), fifteen caregivers (Mage=68.7), and six patients (Mage =70.7) at early stages of dementia. Interviews were audiotaped and then transcribed for analysis. Based on the constant comparative method, three research members independently coded data and collectively developed the themes. Results. Care recipient related risk factors included reduced cognitive capability, limited physical health, social restriction, and the lack of participation in decision making. Risk factors associated with caregivers included caregiver burden and poor coping skills. Community factors consisted of lack of a dementia friendly community that respond to elder abuse and neglect in a preventive manner. Recommended strategies to prevent abuse and neglect included dementia education, more opportunities for social participation, more affordable and accessible long-term care, and training for community service professionals to work with adult protective services. Discussion. Elder abuse and neglect across individuals with dementia or cognitive impairment may occur because of lack of education and skills about coping with dementia. Thus, a dementia-friendly community should be developed by providing more opportunities regarding education and trainings for care recipient, caregivers, and service professionals and changing policies.